Needs Analysis in Education and Training Programs: A Concept of Application - Hamdani; Heni Listiana; Mokhlis; Nuri Wahda Salsabila Usmany (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
In carrying out educational and training activities, needs analysis is the first step that must be carried out by education or training providers, this is because the needs analysis stage is very supportive of the success of the training program to be implemented, training that does not begin with this process makes it difficult for organizers to know what only what is needed by participants and will not be able to predict the success of the program that will be implemented. The aim of this research is to examine the basic concept of needs analysis which in this case is divided into three study focuses, namely: 1) the meaning of needs assessment and training, the benefits of a needs analysis process, and 3) methods and techniques of needs analysis, both from needs assessment, design, materials, and evaluation. The method used in research is the library method, where all forms of data are obtained from literature that is appropriate to the research topic. The primary data source in this research is a study of needs analysis, while secondary data sources are obtained from books, journals, articles and other relevant literature. The data analysis stage in this research uses the condensation stage, data presentation and verification. The results of the research show that 1) This Needs Assessment has the steps of delineating (describing), obtaining (obtaining), and applying (applying) data to obtain certainty about each need. 2) The benefits of needs analysis can be a benchmark and benchmark in making decisions, it can be a view of each activity, time and budget, it can be a solution to existing problems. 3) the needs analysis method can go through several stages such as identifying gaps, developing performance, identifying participants, creating a series of programs to be implemented and estimating costs